The influence of performance measurement systems and supervisor trustworthiness on knowledge sharing - Taufiq, Taufiq; Sholihin, Mahfud (Jurnal Akuntansi dan Auditing Indonesia, 2024)
The objective of our study is to examine the influence of combined performance measurement systems (PMS), which include both subjective evaluation and objective measures, on the willingness of employees to share knowledge. Additionally, our study investigates another variable which may influence subjective judgments of employee performance, namely supervisor trustworthiness. We argue that incorporating subjective evaluations into a performance measurement system will have little effect on knowledge-sharing behavior unless the supervisor is considered trustworthy enough to evaluate such behavior. Using a 2x2 between-subjects experiment design with 73 undergraduate students who act as employees as subjects, the result of this study shows that including subjective evaluation in a PMS encourages the willingness to share knowledge more than only using objective measures. This study also shows that supervisor trustworthiness alone can encourage a willingness to share knowledge. Furthermore, the combination of PMS which include subjective and objective measures and high supervisor trustworthiness has a significant impact on increasing the willingness to share knowledge.